Unusual shocks in our usual models - Filippo Ferroni; Jonas D. M. Fisher; Leonardo Melosi (Federal Reserve Bank of Chicago, 2022)
We propose an event-study research design to identify the nature and propagation of large unusual shocks in DSGE models and apply it to study the macroeconomic effects of the Covid shock. The initial outbreak is represented as the onset of a new shock process where the shock loads on wedges associated with the model's usual shocks. Realizations of the Covid shock come with news about its propagation, allowing us to disentangle the role of beliefs about the future of the pandemic. The model attributes a crucial role to the novel Covid shock in explaining the large contraction in output in the second quarter of 2020 and the rebound in growth expected at the same time. The Covid shock loads significantly on wedges that generate both demand and supply effects but, on net, supply forces dominate. The effects of Covid on hours worked are quite persistent, although the successive pandemic waves (e.g., the Delta wave) have a progressively smaller impact on the macroeconomy. Our methods provide a foundation to estimate structural models with data that include the pandemic without having to specify a micro-founded epidemiological block.
Keywords: C51; E10; E31; E32; E52; 330; Covid-19; pandemic; DSGE models; Survey of Professional Forecasters; business cycles